Poverty Trends in Turkey - Sirma Demir Șeker; Stephen P. Jenkins (Institute for the Study of Labor (IZA), 2013)
This paper provides new evidence about poverty trends in Turkey between 2003 and 2011 and the factors accounting for them. We give particular attention to issues of statistical inference, and the choice of the poverty line and the poverty measure. Our robust conclusion is that absolute poverty declined rapidly between 2003 and 2008 but fell only slightly between 2008 and 2011. Changes in relative poverty were negligible throughout. Using poverty decomposition methods, we argue that the rate of decline in the absolute poverty rate is largely accounted for by changes in the rate of national economic growth rather than by changes in the income distribution or by changes in the distribution of poverty risks across various subgroups within the population or in population composition.
Keywords: I32; D31; C12; 330; poverty; Turkey; poverty dominance